(untitled) (Revista Contexto & Educação, 2023)
This article aims to analyze different contexts and their approximations with different ways of thinking on chemical reactions emerging in the preservice chemistry teachers’ speeches as they study problematizing situations based on the theory of conceptual profiles. Thus, we seek to discuss domains and context models aligned with the assumptions of the theory of conceptual profiles, from structured different ways of thinking and ways of speaking on chemical reactions, considering a historical genesis, social issues, activities, and previous conceptions of individuals that can be associated with specific contexts. We had as participants 21 undergraduate students in a chemistry course for teachers formation, and the data were collected by applying two problematizing situations linked to the concept of chemical reactions. Our results indicate the emergence of different models and domains of contexts, and distinct zones of the conceptual profile of chemical reactions. Thus, we can consider that the chemical reactions are not discussed only from conceptual dimension, but also by articulation among scientific, social and technological views, associated with different ways of thinking the concept in question.